(untitled) (International Journal of Scientific Trends, 2025)
In the article, the importance of tasks of creative description in the formation of interdisciplinary abscissional and ordinate connection of pupils’ thinking in elementary grades is analyzed, and the didactic foundations of mathematical thinking formation are studied.